SYNTHESIS OF NATURAL GELATIN-BASED HARD CAPSULE SHELL FROM CASSAVA STARCH AND HIBISCUS LEAVES GEL - Primata Mardina; Usman Usman; Muhammad Apriliawan Yoga Anggara (Universitas Lambung Mangkurat, 2022)
The aim of this work was to prepare gelatin-based hard capsule shells from natural sources, cassava starch and hibiscus leaves. The effects of composition between cassava starch and hibiscus leaves, and temperature on capsule characteristic was investigated. Extraction and gelatinization were the main method which used in this study. A different compositions of cassava starch and hibiscus leaves gel was added into boiling flask for gelatinization for 2 h. Temperature was maintained at 50, 70 and 100 oC. The optimum resultwas obtained at ratio 8:1 of cassava starch and hibiscus leaves gel with 100 oC operation temperature which has specification 7.60% of ash content, 11.24% of moisture, and 15 min dissolution time.According to the result, this study is expected to be used as a reference for the development of natural gelatin-based hard capsule shell synthesis.